Towards the middle Pleistocene continental glaciation: assessing seasonality in the early Pleistocene of the Mediterranean area - G. Crippa; L. Angiolini; C. Bottini; E. Erba; F. Felletti; C. Frigerio; J. A. I. Hennissen; M. J. Leng; I. Raffi; G. Raineri; M. H. Stephenson (2015)
The Early Pleistocene is a time characterized by high frequency climatic oscillations, which has its lower and upper boundaries coinciding with two important climatic events: the Northern Hemisphere Glaciation and the Middle Pleistocene Transition. The Mediterranean area was strongly affected by the Early Pleistocene climatic changes; one of the most important biotic events is represented by the appearance of the boreal guests at the beginning of the Calabrian Stage, indicating a progressive climatic deterioration in the Mediterranean region. The Arda River marine succession, cropping out in Northern Italy, has been shown to cover this time interval; it is also very rich in macrofossils, and thus it represents an ideal setting to study the climatic oscillations of the Early Pleistocene and understand if and how seasonality varied in this interval using pristine bivalve shells as geochemical archives. We have undertaken bulk isotope analyses on 249 fossil bivalve shells of species of Glycymeris, Aequipecten and Arctica, collected in 141 beds of the Arda section. We have also studied the sclerochemistry of ten pristine bivalve shells belonging to species of Glycymeris and Arctica to reconstruct in detail the seasonality in seven discrete intervals, which we can correlate to the Atlantic Marine Isotope Stages. We show a progressive increase in temperature seasonality through the Early Pleistocene, mostly controlled by cold winters, which became more pronounced toward the Middle Pleistocene Transition. However the isotope data from the bulk shells do not indicate cooling of overall sea surface temperatures throughout the interval, except for a significantly cold event at the first occurrence of the cold taxon Arctica islandica. The increase in seasonality and the arrival of cold guests indicate that the Northern Hemisphere glaciations exerted a strong control on the Mediterranean climate during most of the Early Pleistocene.